Potential mechanism of action of meso-dihydroguaiaretic acid on mycobacterium tuberculosis H37Rv - Clemente Soto, Aldo Francisco; Balderas Rentería, Isaías; Rivera, Gildardo; Segura Cabrera, Aldo; Garza González, Elvira; Camacho Corona, María del Rayo (2014)
The isolation and characterization of the lignan meso-dihydroguaiaretic acid (MDGA) from Larrea tridentata and its activity against Mycobacterial tuberculosis has been demonstrated, but no information regarding its mechanism of action has been documented. Therefore, in this study we carry out the gene expression from total RNA obtained from M. tuberculosis H37Rv treated with MDGA using microarray technology, which was validated by quantitative real time polymerase chain reaction. Results showed that the alpha subunit of coenzyme A transferase of M. tuberculosis H37Rv is present in both geraniol and 1-and 2-methylnaphthalene degradation pathways, which are targeted by MDGA. This assumption was supported by molecular docking which showed stable interaction between MDGA with the active site of the enzyme. We propose that inhibition of coenzyme A transferase of M. tuberculosis H37Rv results in the accumulation of geraniol and 1-and 2-methylnaphtalene inside bacteria, causing membrane destabilization and death of the pathogen. The natural product MDGA is thus an attractive template to develop new anti-tuberculosis drugs, because its target is different from those of known anti-tubercular agents.